Anthropogenic and Climatic Contributions to Observed Carbon System Trends in the Northeast Pacific. Issue 7 (8th July 2021) - Franco, Ana C.; Ianson, Debby; Ross, Tetjana; Hamme, Roberta C.; Monahan, Adam H.; Christian, James R.; Davelaar, Marty; Johnson, William K.; Miller, Lisa A.; Robert, Marie; Tortell, Philippe D.
Abstract: The ocean absorbs anthropogenic carbon, slowing atmospheric CO2 increase but driving ocean acidification. Long‐term changes in the carbon system are typically assessed from single‐point time series or from hydrographic sections spaced by decades. Using higher resolution observations (1–3 year −1 ) from the Line P time series, we investigate processes modulating trends in the carbon system of the northeast subarctic Pacific. Dissolved inorganic carbon (DIC) and apparent oxygen utilization (AOU) from 1990 to 2019 reveal substantial trends over most of the upper water column along the 1, 500 km coastal to open ocean transect. At the surface, an increasing trend in salinity‐normalized DIC (sDIC33 ) (+0.5 ± 0.4 μmol kg −1 yr −1 ) is associated with a decrease in pH (0.01–0.02 decade −1 ) and a decrease in aragonite saturation state (0.04–0.08 decade −1 ). These observed trends are driven by anthropogenic CO2 uptake, partially offset by trends in surface salinity or temperature. Stratification associated with recent marine heat waves appears to have caused anomalously low surface pCO2 . sDIC33 trends of similar magnitude were found below the seasonal thermocline on the 26.7–26.8 isopycnals (150–300 m), which are ventilated in the western Pacific. Roughly, a third (20%–50%) of the subsurface sDIC33 trend is driven by increased remineralization, likely caused by long‐term decreases in ventilation in the western Pacific. Bidecadal oscillations in the ventilation of the 26.7–26.8 isopycnals arising from the Lunar Nodal Cycle cause oscillations in sDIC33 and AOU at the offshore end of our transect. We trace the oscillations to alternating periods of higher anthropogenic carbon uptake or higher carbon remineralization. Plain Language Summary: The ocean takes up anthropogenic carbon and slows the rate at which atmospheric carbon dioxide is increasing. Using 30 years of data from the NE Pacific, we show that the surface ocean is indeed absorbing anthropogenic carbon and undergoing ocean acidification in this region. We find that carbon is also increasing in the subsurface waters. This excess carbon was absorbed in the western Pacific, where dense waters sink from the surface to the subsurface and transport anthropogenic carbon and oxygen eastward. This western Pacific breathing process appears to be weakening in time. If this trend continues, less anthropogenic carbon will be taken up and stored in subsurface waters in the future. Despite this reduction, some carbon will still naturally accumulate as the available oxygen is consumed and natural carbon dioxide is produced. Using data from three decades, we demonstrate the impact of climatic events and natural variability on the carbon system. At the surface, recent marine heat waves have reduced the amount of carbon absorbed by the ocean. In the subsurface waters, we observed that anthropogenic carbon increased in decades with stronger ventilation, while natural carbon generated by respiration of organic matter increased during periods of weaker ventilation. Key Points: Local uptake of anthropogenic CO2 decreases surface pH in the NE Pacific but the trend appears modulated by recent temporal variability Declining ventilation in the NW Pacific appears responsible for 20%–50% of the inorganic carbon increase in NE Pacific intermediate water The signature of tidally driven bidecadal oscillations propagates east to Line P producing fluctuations in intermediate water preformed DIC